Embracing the Meta-Copernican Turn: Non-decomposition and Mechanistic Explanations. Issue 2 (3rd April 2018) - Meyer, Russell
Abstract: In line with proponents of 4E cognition, Gallagher [2019 ] is concerned that many cognitive phenomena are not amenable to decomposition strategies since their very nature is to be constituted extensively. By contrast the received view on causal explanation—the mechanistic account [Craver2007 ]—emphasises the necessity for decomposition in explaining natural phenomena and insists on a sharp distinction between causal versus constitutive relations. I propose that removing the requirement that constitutive relations cannot also be causes helps to ease this tension between explanation and Gallagher's non-decompositional stance, per Leuridan [2012 ]. Further, I draw on Froese et al.'s [2013] minimal model of social cognition to argue that constitutive relations can and do act as causal difference-makers in the Woodwardian sense [Woodward2003 ].